2023
DOI: 10.1523/eneuro.0336-22.2023
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Cortical Neurons to Intracortical Microstimulation in Awake Primates

Abstract: Intracortical microstimulation (ICMS) is commonly used in many experimental and clinical paradigms; however, its effects on the activation of neurons are still not completely understood. To document the responses of cortical neurons in awake non-human primates to stimulation, we recorded single-unit activity while delivering single-pulse stimulation via Utah arrays implanted in primary motor cortex of three macaque monkeys. Stimuli between 5-50 μA delivered to single channels reliably evoked spikes in neurons … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 55 publications
3
8
0
Order By: Relevance
“…Consistent with prior studies we found that intracortical microstimulation generally produced a biphasic neuronal response consisting of an early increase in firing within 10 ms followed by a transient suppression of 100 ms or so (Butovas and Schwarz, 2003;Sombeck et al, 2022;Yun et al, 2023). This biphasic pattern was conserved at all levels of anesthesia although the spike rate increases were lower during anesthesia than in the awake state.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Consistent with prior studies we found that intracortical microstimulation generally produced a biphasic neuronal response consisting of an early increase in firing within 10 ms followed by a transient suppression of 100 ms or so (Butovas and Schwarz, 2003;Sombeck et al, 2022;Yun et al, 2023). This biphasic pattern was conserved at all levels of anesthesia although the spike rate increases were lower during anesthesia than in the awake state.…”
Section: Discussionsupporting
confidence: 91%
“…Stimulation pulses were charge-balanced, biphasic waveforms (Merrill et al, 2005) that were initially varied with respect to cathodic-anodic temporal order and asymmetry of duration and amplitude. Preliminary tests with 5, 10, 20, and 40 μA stimulation currents showed that maximum response was afforded by 40 μA in agreement with other studies (Voigt and Kral, 2019;Sombeck et al, 2022;Yun et al, 2023). Therefore, in subsequent experiments a maximum stimulus current of 40 μA was used.…”
Section: Methodssupporting
confidence: 90%
See 2 more Smart Citations
“…Butovas and colleagues quantified the temporal response to ICMS of neurons in the somatosensory cortex (S1) of rats [1,13]. At stimulation threshold, single pulse ICMS evoked a short latency excitatory response followed by long-lasting inhibition [1], and a number of other groups subsequently replicated these findings [2,11,12,[14][15][16][17][18][19][20][21][22]. The strength of short-latency excitation increased, and the duration of the inhibition became longer, with increased stimulation intensity [11,12].…”
Section: Introductionmentioning
confidence: 99%